(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
Folklore the beginning of the art of words, has been a constant companion of people’s life in every era. In the second half of the 19 th century, Nurota and Bulungur schools, which were the major centers of folk art appeared. In the research, it was noted that V.Abdullayev wrofe many such works of oral creativity among the uzbek, Turkmen, Karakalpak and Kazakh peoples in the 18th-19th centuries and had appositive impact on the development of written literature.It is reflected that the scientific -theoretical views on the nature of flok books, which are considered acommon phenomenon of folk studies, served as the result of the first researches in the history of uzbek literary studies.